2018
DOI: 10.1016/j.bbr.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorder and altered locomotor activity as biomarkers of the Parkinson’s disease cholinopathy in rat

Abstract: In order to find out the possible earliest biomarkers of Parkinson's disease (PD) cholinopathy, we followed the impact of bilateral pedunculopontine tegmental nucleus (PPT) lesion in rat on: the cortical and hippocampal sleep/wake states architectures, all sleep states related EEG microstructures, sleep spindles, the basal and stimulated locomotor activity. Sleep and basal locomotor activity in adult Wistar rats were followed during their inactive circadian phase, and throughout the same aging period. The bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(61 citation statements)
references
References 52 publications
0
58
1
Order By: Relevance
“…On the other hand, the increased density of prolonged HVS in the motor cortex versus increased density of slower and shorter HVS in the hippocampus, during their simultaneous REM sleep, in the rat model of PD cholinopathy, reflects serious rearrangements within the thalamo‐cortical regulatory network, as a result of the tonically and sustainably decreased inhibition of RT neurons and the excitation of TC neurons (Ciric et al, ). In addition, a recent study has suggested that pentobarbital anaesthesia is highly beneficial for post‐anaesthesia REM sleep in the physiological condition as well as during PD cholinergic neuropathology in rats (Lazic et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the increased density of prolonged HVS in the motor cortex versus increased density of slower and shorter HVS in the hippocampus, during their simultaneous REM sleep, in the rat model of PD cholinopathy, reflects serious rearrangements within the thalamo‐cortical regulatory network, as a result of the tonically and sustainably decreased inhibition of RT neurons and the excitation of TC neurons (Ciric et al, ). In addition, a recent study has suggested that pentobarbital anaesthesia is highly beneficial for post‐anaesthesia REM sleep in the physiological condition as well as during PD cholinergic neuropathology in rats (Lazic et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The first step for automatic SS and HVS detection during the 1 hr of NREM or REM sleep for each rat and experimental group was to filter the EEG signals using the 11–17 Hz band pass filter for SS, or the 4.1–10 Hz band pass filter for HVS. Then, we applied the continuous wavelet transform with the mother wavelet “cmorl‐2’’ MATLAB R2011a function, providing a complex Morlet wavelet with a determined central frequency f 0 = 2 (Adamczyk, Genzel, Dresler, Steiger, & Friess, ; Ciric et al, ). In addition, all the SS had a minimal duration of 0.5 s, whereas all the HVS had a minimal duration of 1 s. However, because we automatically detected many false positive or negative SS or HVS, we had to visually correct all the automatically detected SS or HVS for their final extraction from each NREM/REM sleep episode of each rat and each experimental group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations